2020
DOI: 10.15537/smj.2020.12.25576
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the cognitive status of older adults attending primary healthcare centers in Saudi Arabia using the Mini-Mental State Examination

Abstract: Objectives: To assess the cognitive status of older adults in Saudi Arabia. Methods: This was a cross-sectional, multistage, stratified study of older individuals (≥60 years of age) attending primary healthcare centres in Riyadh, Saudi Arabia between January 2015 and April 2017. We collected data using a structured questionnaire, which incorporated questions regarding demographic and anthropometric variables, the Arabic version of Mini-Mental State Examination, the Mini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 53 publications
0
10
0
1
Order By: Relevance
“…A cross-sectional multistage study that involved 1299 older individuals attending PHCCs in Riyadh between January 2015 and April 2017, using the Arabic version of the Mini-Mental State Examination (MMSE); found that 21% of the studied population had cognitive impairment. 29 Furthermore, a community-based study in 2018 among 170 persons aged ≥60 years using the Arabic version of the Montreal Cognitive Assessment (MoCA) test reported the prevalence of cognitive impairment to be 45%, mild cognitive impairment to be 38.6%, and dementia at 6.4%. 30 In addition, a recent study in Portugal that assessed the prevalence and incidence of cognitive impairment in the elderly population (65-85 years old) reported the prevalence of cognitive impairment to be 15.5%.…”
Section: Discussionmentioning
confidence: 99%
“…A cross-sectional multistage study that involved 1299 older individuals attending PHCCs in Riyadh between January 2015 and April 2017, using the Arabic version of the Mini-Mental State Examination (MMSE); found that 21% of the studied population had cognitive impairment. 29 Furthermore, a community-based study in 2018 among 170 persons aged ≥60 years using the Arabic version of the Montreal Cognitive Assessment (MoCA) test reported the prevalence of cognitive impairment to be 45%, mild cognitive impairment to be 38.6%, and dementia at 6.4%. 30 In addition, a recent study in Portugal that assessed the prevalence and incidence of cognitive impairment in the elderly population (65-85 years old) reported the prevalence of cognitive impairment to be 15.5%.…”
Section: Discussionmentioning
confidence: 99%
“…Despite using different methodology, our results are in agreement with a recent study by Alshammari et al in 2020, which used the MMSE in the same setting (primary healthcare) with 1299 participants. They found the prevalence of MCI to be around 17% and that of severe cognitive impairment to be 3.8% [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this way, there is a positive relationship between the physiotherapists in maintaining better chances to live a healthy life. This study is evident that physiotherapists are a major part of every society, which helps the public to keep efforts for their health [19]. Primary healthcare is needed for people to check on the increased risks of the diseases.…”
Section: Review Of Literaturementioning
confidence: 94%
“…The reduction in the ratio of these diseases is vital to improving the health of the people. Therefore, the role of physiotherapists is determining factor for the health of the people and great leads to creating a better way of life for them [19]. The number of primary healthcare issues is handled by physiotherapists who significantly help the public to keep a check on the health issues.…”
Section: Review Of Literaturementioning
confidence: 99%